Geriatric nutritional risk index has a prognostic value for recovery outcomes in elderly patients with brain abscess - Pei, Xu; Zhang, Yutu; Jiang, Dongfeng; Zhang, Meng; Fu, Junyan; Niu, Yang; Tian, Mi; Huang, Shanshan (Frontiers in Nutrition, 2024)
Background The Geriatric Nutritional Risk Index (GNRI) is a straightforward and objective tool for nutritional screening in older patients and has been demonstrated to possess prognostic predictive value in several diseases. Nonetheless, there is a lack of research on the nutritional risk associated with brain abscess in the older. This study aimed to evaluate the prevalence of nutritional risk among these patients by GNRI and to investigate its potential prognostic value for clinical outcomes. Materials and methods From August 2019 to April 2023, 100 older patients diagnosed with brain abscess were enrolled in this single-center prospective cohort study, which evaluated the prognostic value of the Geriatric Nutritional Risk Index (GNRI) in elderly brain abscess patients. Data collected included demographic, and clinical characteristics at admission and calculated the GNRI, and the Glasgow Outcome Scale (GOS) score 6 months post-discharge. A GOS score of 5 was considered indicative of a good recovery, whereas scores ranging from 1 to 4 were classified as poor recovery. Results The results revealed that 48% of older brain abscess patients were at risk of malnutrition according to the GNRI. These patients had significantly higher post-admission C-reactive protein (CRP) levels (p = 0.017), more comorbidities (p < 0.001), and higher age-adjusted Charlson Comorbidity Index (aCCI) scores (p < 0.001) compared to those without nutritional risk. Spearman correlation analysis showed that GNRI scores were negatively correlated with CRP levels, comorbidities, and aCCI scores, and positively correlated with Glasgow Outcome Scale (GOS) scores (Spearman’s ρ = 0.624, p < 0.001). Multivariate logistic regression revealed that lower GNRI values were linked to reduced GOS levels (OR = 0.826, 95% CI: 0.775–0.880). ROC analysis determined a GNRI threshold of 97.50 for predicting poor recovery, with 90.57% sensitivity and 87.23% specificity. Conclusion The older brain abscess patients exhibited a high malnutrition risk. GNRI showed an important predictive value for recovery in older patients, which could be helpful in clinical intervention and rehabilitation.